Is neostigmine effective in severe pufferfish-associated tetrodotoxin poisoning?. (January 2015) - Liu, Su-Hsun; Tseng, Chiung-Yao; Lin, Chih-Chuan
Abstract Context. Pufferfish-associated tetrodotoxin poisoning occurs occasionally in coastal regions of Asian countries and sporadically elsewhere. While anecdotal reports have suggested neostigmine use, evidence for its clinical effectiveness remains unclear. Objective. We sought to determine whether neostigmine was likely to be effective in tetrodotoxin-poisoned patients with acute respiratory failure caused by pufferfish consumption. Methods. We searched in PubMed, EMBASE, CINAHL, Google Scholar, and other databases to collect cases of acute pufferfish-associated tetrodotoxin poisoning ever published without limiting publishing years. We screened each identified title and abstracts that were published in English language, selected, and reviewed full-text publications that were published in English or Chinese and reported at least one adult case (aged ≥ 16 years) of acute respiratory failure attributable to pufferfish-associated tetrodotoxin poisoning. Results. Overall, we identified 435 titles and retrieved 71 full-text publications for further review. After excluding duplicates, review articles, articles reporting cases of minor severity only, incomplete clinical information or non-tetrodotoxin poisoning, and non-English, non-Chinese articles, we selected 37 citations (23 case series and 14 case reports) for data extraction and evidence synthesis. Clusters of acute pufferfish poisoning were mostly reported from coastal countries in the western Pacific or in the Indian Ocean, whereas sporadic cases have occurred in Mediterranean countries and Puerto Rico. Although 10 of the 14 case series reported neostigmine use in respiratory failure, age of these cases was not separately reported. Group-level outcome reporting irrespective of severity or the universal use of neostigmine in severe cases did not allow separate quantitative synthesis of evidence. In contrast, 32 cases from the other 9 case series and 14 case reports had individual information available for pooled analysis, yet only three of which were given neostigmine. Conclusion. Both qualitatively and quantitatively, the current literature was insufficient to provide an evidence base for or against the use of neostigmine in adults with tetrodotoxin-associated respiratory failure. This lack of quality evidence has mainly resulted from poor reporting in published case series. More research in collaborative data collection using standardized reporting and in animal experiments may be needed to tackle this problem. In addition, future case reports should adhere to the CARE guidelines to facilitate experience sharing, evidence synthesis, and consensus forming.